Frontier studies on highly selective bio-regulators useful for environmentally benign agricultural production. Issue 6 (3rd June 2015) - Hayashi, Hideo
Abstract: Fungal metabolites active for insects were obtained from fermentation products using okara media. The mechanisms of action of these compounds against insects were clarified using voltage clamp electrophysiology. The branching factor inducing hyphal branching in arbuscular mycorrhizal (AM) fungi was isolated from the root exudates of Lotus japonicus and identified as 5-deoxystrigol. Strigolactones were originally identified as seed germination stimulants of parasitic weeds; therefore, synthetic strigolactones were developed to exhibit the inducing activity of hyphal branching in AM fungi and diminish the stimulating activity of seed germination of parasitic weeds. Signaling molecules, acylhomoserine lactones (AHLs), in quorum sensing were identified in the fungal strain Mortierella alpina A-178, and the true producer of AHLs was clarified as symbiotic bacteria in the fungus. Since acyl-( S )-adenosylmethionine analogs may be good candidates for competitive inhibitors of AHL synthases, intermediate mimics in the biosynthesis of AHLs have been synthesized. Abstract: : Structures of bioactive compounds